Peranan Digital Accounting Berbasis Accurate Terhadap Laporan Keuangan Pada PT Kurnia Eka Nusa - Yuli Meliana; Joanne Intania Rut Simunapendi; Rizka Maya Shova; Maria Yovita R.Pandin (Jurnal Riset Akuntansi, 2023)
The purpose of the research is to find out whether the role of accurate-based digital accounting is useful, appropriate and in accordance with what is needed by PT Kurnia Eka Nusa in presenting its financial statements. In the form of qualitative research with observation, interview and documentation methods. The results obtained that accurate-based digital accounting at PT Kurnia Eka Nusa in terms of the role of accurate, the differences before and after using accurate-based digital accounting and the advantages and disadvantages of using accurate in presenting financial statements PT Kurnia Eka Nusa stated that accurate helps present financial statements but accurate is not the best software for now.